Treasury Circular 2/2005-Malay Version - Universiti Malaysia Sarawak, Centre for Applied Learning and Multimedia (Centre for Applied Learning and Multimedia, 2005)
No Rujukan : KK/BP108/79/6-1Jld.5(SK.1/2005)